INFANTS' INTESTINAL COLICS. MODERN DATA - N.I. Ursova ("Paediatrician" Publishers LLC, 2011)
The article analyzes modern data on infants' intestinal colics. Peculiarities of nutrition, intestinal microbiocenose in healthy infants, methods of colcs' correction are discussed. Author describes the principles of probiotics choice based on their clinical effectiveness in infants. Milk formula «Nan Comfort» can be useful in prophylaxis and treatment of functional disorders of gastrointestinal tract in children. Key words: infants, gastrointestinal tract, anatomy, physiology, intestinal colics, nutrition, probiotics. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (2): 125-131)